OPTIMALISASI INPUT USAHA TANI PADI (Studi Kasus Desa Clumprit Kecamatan Pagelaran Kabupaten Malang) - Suriaatmaja, M Erwan (Universitas 17 Agustus 1945 Samarinda, 2015)
Optimization Of Input Farming Rice (Case Study Clumprit Rural District of Pagelaran Malang). This research aims to know (1) the effect of output factor use for the optimization of rice farming business input (2) to know the economic efficiency of rice farming business factor.This research is conducted on October 2013 until March 2014 in Clumprit village, Pagelaran District, Malang Regency. The data collection is done by survey method namely by observation, group discussion and interview; the Secondary data is collected from the documents namely: village monograph. The data analysis method used is production function analysis of Douglass and Marginal Product Value analysis.The research result shows that ; (1) the affecting factors to the rice farming business are fertilizer and seed in each stratum, so the use of the input factor is more for the necessary portion; (2) The farmer income in the 2nd planting period is higher tan the 1st planting period; and (3) The rice farming business in Clumprit Village, for the Marginal Product Value analysis for each stratum both in the 1st and 2nd periods is inefficient.